Genome-wide identification of Glycyrrhiza uralensis Fisch. MAPK gene family and expression analysis under salt stress relieved by Bacillus subtilis - Gao, Pengchao; Xiao, Jiancai; Guo, Wanying; Fan, Rui; Zhang, Yan; Nan, Tiegui (Frontiers in Genetics, 2024)
Research on Glycyrrhiza uralensis, a nonhalophyte that thrives in saline-alkaline soil and a traditional Chinese medicinal component, is focused on improving its ability to tolerate salt stress to increase its pro ductivity and preserve its "Dao-di" characteristics. Furthermore, the inoculation of bioagents such as Bacill us subtilis to increase plant responses to abiotic stressors is currently a mainstream strategy. Mitogen-activ ated protein kinase (MAPK), a highly conserved protein kinase, plays a significant role in plant responses to various abiotic stress pathways. This investigation involved the identification of 21 members of the Gu MAPK family from the genome of G. uralensis, with an analysis of their protein conserved domains, gene structures, evolutionary relationships, and phosphorylation sites using bioinformatics tools. Systematic evol utionary analysis of the 21 GuMAPKs classified them into four distinct subgroups, revealing significant dif ferences in gene structure and exon numbers. Collinearity analysis highlighted the crucial role of segmenta l duplication in expanding the GuMAPK gene family, which is particularly evident in G. uralensis and sh ows a close phylogenetic relationship with Arabidopsis thaliana, tomato, and cucumber. Additionally, the i dentification of phosphorylation sites suggests a strong correlation between GuMAPK and various physiolog ical processes, including hormonal responses, stress resistance, and growth and development. Protein interac tion analysis further supported the role of GuMAPK proteins in regulating essential downstream genes. Thr ough examination of transcriptome expression patterns, GuMAPK16-2 emerged as a prospective pivotal reg ulatory factor in the context of salt stress and B. subtilis inoculation, a finding supported by its subcellula r localization within the nucleus. These discoveries offer compelling evidence for the involvement of GuM APK in the salt stress response and for the exploration of the mechanisms underlying B. subtilis' enhance ment of salt tolerance in G. uralensis. Article II.